Effect of SiO2 nanoparticles on drought resistance in hawthorn seedlings - Ashkavand, Peyman; Struve, Daniel; Tabari, Masoud; Tomášková, Ivana; Zarafshar, Mehrdad (Leśne Prace Badawcze, 2015)
Drought is a significant factor limiting crop production in arid regions while hawthorns ( Crataegus sp.) are an important component of such region’s forests. Therefore, treatments that increase hawthorn drought resistance may also increase transplanting success. Thus, the physiological and biochemical responses of hawthorn seedlings to a factorial combination of different concentrations of silica nanoparticles (SNPs at 0, 10, 50 and 100 mg L -1 ) and three soil moisture treatments (without stress, moderate stress and severe stress) were investigated. Seedlings were irrigated with one of the four concentrations of SNPs for 45 days before exposing them to drought stress. Photosynthesis parameters, malondialdehyde (MDA), relative water content (RWC), membrane electrolyte leakage (ELI) as well as chlorophyll, carotenoid, carbohydrate and proline content were determined. At the end of the experiment, positive effects by SNP pre-treatment on physiological indexes were observed during drought stress. Under drought conditions, the effect of SNPs on photosynthetic rate and stomatal conductance was evident. Although the SNPs increased plant biomass, xylem water potential and MDA content, especially under drought conditions, RWC and ELI were not affected by the SNP pre-treatments. Seedlings pre-treated with SNPs had a decreased carbohydrate and proline content under all water regimes, but especially so under drought. Total chlorophyll content and carotenoid content did not change among the treatments. Generally, the findings imply that SNPs play a positive role in maintaining critical physiological and biochemical functions in hawthorn seedlings under drought stress conditions. However, more studies are needed before the physiological and biochemical basis of induced drought resistance can be determined.